A Brief Atlas of Insulin - Ayan, Esra; DeMirci, Hasan (Current Diabetes Reviews, 2023)
Insulin is an essential factor for mammalian organisms: a regulator of glucose metabolism and other key signaling pathways. Insulin is also a multifunctional hormone whose absence can cause many diseases. Recombinant insulin is widely used in the treatment of diabetes. Understanding insulin, biosimilars, and biobetters from a holistic perspective will help pharmacologically user-friendly molecules design and develop personalized medicine-oriented therapeutic strategies for diabetes. Additionally, it helps to understand the underlying mechanism of other insulindependent metabolic disorders. The purpose of this atlas is to review insulin from a biotechnological, basic science, and clinical perspective, explain nearly all insulin-related disorders and their underlying molecular mechanisms, explore exogenous/recombinant production strategies of patented and research-level insulin/analogs, and highlight their mechanism of action from a structural perspective. Combined with computational analysis, comparisons of insulin and analogs also provide novel information about the structural dynamics of insulin.
Keywords: Insulin dynamics